2015
DOI: 10.3390/ijms16022794
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of Single-Stranded DNA Molecular Recognition Elements against S. aureus Alpha Toxin and Sensitive Detection in Human Serum

Abstract: Alpha toxin is one of the major virulence factors secreted by Staphylococcus aureus, a bacterium that is responsible for a wide variety of infections in both community and hospital settings. Due to the prevalence of S. aureus related infections and the emergence of methicillin-resistant S. aureus, rapid and accurate diagnosis of S. aureus infections is crucial in benefiting patient health outcomes. In this study, a rigorous Systematic Evolution of Ligands by Exponential Enrichment (SELEX) variant previously de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
(77 reference statements)
1
19
0
Order By: Relevance
“…Fluorescence plate based cross-binding assay showed the selection ssDNA MRE was two to five times more selective on toxin B than negative targets. A proof-of-concept modified ELISA using ssDNA as the toxin capturing element was developed and able to detect toxin B at 50 nM concentration in human fecal matter [ 111 ].…”
Section: In Vitro Selection Of Ssdna Molecular mentioning
confidence: 99%
“…Fluorescence plate based cross-binding assay showed the selection ssDNA MRE was two to five times more selective on toxin B than negative targets. A proof-of-concept modified ELISA using ssDNA as the toxin capturing element was developed and able to detect toxin B at 50 nM concentration in human fecal matter [ 111 ].…”
Section: In Vitro Selection Of Ssdna Molecular mentioning
confidence: 99%
“…Therefore, several ssDNA aptamers have been developed against staphylococcal enterotoxins (SEs). To develop potential diagnostic agents, aptamer APT SEB1 for staphylococcal enterotoxin B (SEB), 42 aptamer C10 for S. aureus enterotoxin C1 (SEC1), 43 aptamer R12.06 for α-toxin, 44 aptamer Antibac1 and Antibac2 for a peptidoglycan 45 and aptamer PA#2/8 for protein A 46 were generated for the detection of SEs. Among these aptamers, aptamer R12.06 for αtoxin was utilized in a modified sandwich ELISA and sensitive detection of 200 nM a-toxin in undiluted human serum samples was achieved.…”
Section: S Aureusmentioning
confidence: 99%
“…Among these aptamers, aptamer R12.06 for αtoxin was utilized in a modified sandwich ELISA and sensitive detection of 200 nM a-toxin in undiluted human serum samples was achieved. 44 The first ssDNA aptamers specific to whole cells for S. aureus detection were introduced by Cao et al in 2009. 47 They obtained a panel of ssDNA aptamers specific to S. aureus and have demonstrated that five aptamers (SA20, SA23, SA31, SA34 and SA43) recognize different molecular targets on S. aureus and have strong affinity, with K d values in the nanomolar range.…”
Section: S Aureusmentioning
confidence: 99%
“…A modified enzyme-linked immunosorbent assay (ELISA) method was developed by using an aptamer with high affinity and specificity. The limitation of this technique for detection was 200 nmol l À1 in undiluted human serum specimen (Hong et al 2015). Other DNA aptamers were developed via the SELEX technique, which specifically inhibited the cytotoxic activity of a-toxin.…”
mentioning
confidence: 99%